Fault Reassessment in Way Huwi Area, South Lampung using Gravity Method - LUHUT PARDAMEAN SIRINGORINGO; Andri Yadi Paembonan; Virgian Rahmanda (Himpunan Ahli Geofisika Indonesia (HAGI), 2021)
The Age majority of regional geological maps that have been referenced by geologists in Indonesia are about 20-30 years old. One of them is Tanjung Karang Geological Map. Our opinion is that the map is old enough. Some faults features are doubted in the aspect of existence and its trend. It is represented by the dashed line symbol in the maps. Therefore, this research was carried out to provide a more detailed reinterpretation of faults in the Way Huwi area using the Gravity method. This area was selected because it is the new education center and economy in the eastern part of Bandar Lampung. This research was also carried out as part of disaster mitigation. The faults within this research area were identified with Horst-Graben type and formed before Lampung Formation was deposited. The trend of these normal faults is Northeast-Southwest. it is very different from the fault interpretation on Tanjung Karang regional geology map with the Northwest-Southeast direction. The genesis of the Way Huwi Fault is indirectly part of the extensional Sunda Strait.